The Glutathione Metabolite γ-Glutamyl-Glutamate Partially Activates Glutamate NMDA Receptors in Central Neurons With Higher Efficacy for GluN2B-Containing Receptors - Sebih, Fatiha; Mokrane, Nawfel; Fontanel, Pierre; Kayatekin, Mete; Kaabeche, Mahira; Guiramand, Janique; Cohen-Solal, Catherine; Cens, Thierry; Rousset, Matthieu; Charnet, Pierre; De Jésus Ferreira, Marie-Céleste; Thibaud, Jean-Baptiste; et al. (Frontiers in Pharmacology, 2022)
The gamma-L-glutamyl-L-glutamate (gamma-Glu-Glu) was synthetized and further characterized for its activity on cultured neurons. We observed that gamma-Glu-Glu elicited exciting effects on neurons likely by activating mainly N-methyl-D-aspartate (NMDA) receptors. These effects were dependent on the integrity of synaptic transmission, as they were blocked by tetrodotoxin (TTX). We next evaluated its activity on NMDA receptors by testing it on cells expressing these receptors. We observed that gamma-Glu-Glu partially activated NMDA receptors and exhibited better efficacy for NMDA receptors containing the GluN2B subunit. Moreover, at low concentration, gamma-Glu-Glu potentiated the responses of glutamate on NMDA receptors. Finally, the endogenous production of gamma-Glu-Glu was measured with LC-MS on the extracellular medium of C6 rat astroglioma cells. We found that extracellular gamma-Glu-Glu concentration was, to some extent, directly linked to GSH metabolism, as gamma-Glu-Glu can be a by-product of glutathione (GSH) breakdown after gamma-glutamyl-transferase action. Therefore, gamma-Glu-Glu could exert excitatory effects by activating neuronal NMDA receptors when GSH production is enhanced.